2020
DOI: 10.3390/ejihpe10030065
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Women Workplace Culture Scale: Validation and Psychometric Properties of a Three-Factor Structure in an Iranian Study Sample

Abstract: This paper describes the validation process of the Persian version of the Women Workplace Culture Scale and provides information about the perception of this culture in an Iranian working environment. A 30-item Persian version of the Women Workplace Culture (WWC) Questionnaire was administered to women working in public departments of the city of Bojnord, Iran (N = 200). As a result of a theory- and data-driven bottom-up empirical approach, a reduced 10-item three-dimensional scale was achieved entailing (I) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
1
0
3
Order By: Relevance
“…Additionally, there may be differences in civic behavior at work among employees from different national cultures due to variations in implicit norms for expressing disagreement between collectivistic and individualistic cultures (Costa, 2014;Liu, 2020;Ahmed Elsayed et al, 2021;Alam et al, 2021;Gupta and Singh, 2021;Hossny and Sabra, 2021;Sawada et al, 2021). In today's diverse workplaces, understanding these differences can enhance communication and collaboration among workers (Chandolia and Anastasiou, 2020;Lv et al, 2020;Toscano et al, 2020). Finally, empirical research should investigate the potential impact of leaders' responses when confronted with employees' uncivil behavior (Porath et al, 2015;Laschinger and Read, 2016), as these reactions are observed by colleagues and may influence long-term outcomes, such as perceptions of organizational justice (Yanchus et al, 2017).…”
Section: Implications For Future Research Intervention and Social Pol...mentioning
confidence: 99%
“…Additionally, there may be differences in civic behavior at work among employees from different national cultures due to variations in implicit norms for expressing disagreement between collectivistic and individualistic cultures (Costa, 2014;Liu, 2020;Ahmed Elsayed et al, 2021;Alam et al, 2021;Gupta and Singh, 2021;Hossny and Sabra, 2021;Sawada et al, 2021). In today's diverse workplaces, understanding these differences can enhance communication and collaboration among workers (Chandolia and Anastasiou, 2020;Lv et al, 2020;Toscano et al, 2020). Finally, empirical research should investigate the potential impact of leaders' responses when confronted with employees' uncivil behavior (Porath et al, 2015;Laschinger and Read, 2016), as these reactions are observed by colleagues and may influence long-term outcomes, such as perceptions of organizational justice (Yanchus et al, 2017).…”
Section: Implications For Future Research Intervention and Social Pol...mentioning
confidence: 99%
“…Berbagai bentuk diskriminasi gender di tempat kerja dapat dikelompokkan dalam beberapa aspek meliputi hambatan pengembangan karier (perceived societal barriers for career development), hambatan organisasional (perceived organizational barriers), hingga pelecehan seksual (sexual harassment) di tempat kerja (Toscano, Giusino, & Pordanjani, 2020).…”
Section: Pendahuluanunclassified
“…Faktor utama terjadinya diskriminasi gender di Indonesia adalah konstruksi budaya yang berlaku, yaitu budaya patriarki yang meyakini bahwa laki-laki adalah kelompok gender yang wajib bekerja, sedangkan perempuan adalah kelompok gender yang bertugas mengurus rumah tangga (Nuraeni & Suryono, 2021). Fenomena diskriminasi gender di tempat kerja sendiri merupakan cerminan kerangka nilai, keyakinan, dan norma dalam organisasi yang kemudian mempengaruhi bagaimana pekerja berpikir dan bersikap terhadap organisasi (Toscano et al, 2020), termasuk kaitannya dengan kemunculan turnover intention.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation